Achara in the Period of the First Apostles - Diasamidze, Bichiko (Actual Problems of Kartvelology, 2025)
Historical Adjara covered the gorge of Adjaristskali and surrounding territories of Batum-Kobuleti. In the period of the apostles of Christ (I-II centuries) these territories were populated by Dzidriti triebs. At this time one part of Adjara, situated in the South of the river Chorokhi and including GonioApsarosi, was incorporated into the kingdom of Makron-Heniokh subordinated to Rome and the gorge of Adjaristskali with Batum-Kobuleti into the Kingdom of Kartli. Under such conditions Adjara played a role of bulwark for both Egrisi and Kartli. After resurrection of Christ, his Apostles (Saint Andrew the First Called, Simon Cananeus, Matthew) visited Did-Adjara and preached a New Testament. They built churches, installed the priests… It can be admitted that it was the first church in Georgia… Since Christianity has become the symbol of spiritual and cultural-political unity of the Georgian people.